Assessing the Quality of Internet of Things (IoT) Medical Application - Teeba Ismail Kh.; Banar Fareed Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The number of applications that use internet of things (IoT) concepts is rapidly increasing. Without high-quality assurance, this growth cannot continue. According to the literature, quality assurance (QA) models for internet of things software applications are needed urgently. The goal of this study is to build a model-based testing framework for assessing the performance quality of one of the IoT applications. A real-world IoT case implementations have been modeled and analyzed in order to determine the output quality attributes. For software quality assurance applications, the International Organization for Standardization (ISO 25000) quality model was used. The case study consists of thousands of combinations of test cases, which are mostly beyond the capabilities of the resources for achieving the target in the right time. To solve this problem ACTS has been introduced to reduce the case dimensions and find the optimum cases. Finally, all these techniques have been integrated to a new model-based approach called Model-Based Testing for Performance Attribute (MBTPA). The MBTPA has been applied to the case successfully.